Respons Penyelenggaraan Perjalanan Ibadah Umrah terhadap Larangan Memfasilitasi Dana Talangan dalam PMA No 8 Tahun 2018 - Riskyi Nurdiawati; Agus Wahyu Triatmo (Academic Journal of Da'wa and Communication, 2021)
This research aims to analyze the policy of paying the hajj bailout funds carried out by means of a monthly scheme after the pilgrims return from the Holy Land. This is contrary to PMA No.8 of 2018Â which statesÂ that PPIU is prohibited from facilitating congregations using bailout funds. However, this is still being implemented by PPIU in Surakarta even though they are guided by PMA. The research method used in this research is descriptive qualitative. The data sources were explored by interview and policy documentation. It was concluded that the PPIU response in Surakarta to PMA No. 8 of 2018 did not expect that there was a ban on facilitating congregations to use the bailout funds because PPIU provided all the same facilities and services as regular congregations. PPIU in increasing the number of congregants had made several programs, one of which was the bailout funds. The society interest in using the bailout funds reaches 50%. The bailout fundsÂ couldÂ help the middle and lower class economic community to carry out the Umrah pilgrimage. The bailout program was organized by a third party in the financial provider. The bailout fund was not part of the PPIU program so that it was considered not a problem because it was carried out openly and the Ministry of Religious Affairs did not carry out supervision from the start starting from the financing or PPIU. The lack of supervision by the Ministry of Religious Affairs became a factor in the occurrence of violations.